2016
DOI: 10.1080/00224545.2016.1176551
|View full text |Cite
|
Sign up to set email alerts
|

Attitude similarity and familiarity and their links to mental health: An examination of potential interpersonal mediators

Abstract: Similarity and familiarity with partner's attitudes (Byrne, Clore, & Smeaton, 1986; Sanbonmatsu, Uchino, & Birmingham, 2011) are linked to positive relationship outcomes, while interpersonal variables have been linked to mental health (e.g., Lakey & Cronin, 2008). Using multilevel models (MLMs), we modeled the associations between these attitudinal variables and mental health outcomes in 74 married couples. We found that higher levels of attitude similarity in couples were linked to lower depression, while hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In a similar vein, it would be interesting to examine whether sharing the experience of attitudinal conflict has positive effects on individual and interpersonal well-being. For example, in the domain of close relationships, previous research showed that (univalent) attitude similarity between partners is negatively associated with depression ( Moore et al, 2017 ). It is plausible that the identification of those topics that partners feel similarly torn about could be good guidance for partner therapy to strengthen both the relationship and the partners’ well-being in it.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, it would be interesting to examine whether sharing the experience of attitudinal conflict has positive effects on individual and interpersonal well-being. For example, in the domain of close relationships, previous research showed that (univalent) attitude similarity between partners is negatively associated with depression ( Moore et al, 2017 ). It is plausible that the identification of those topics that partners feel similarly torn about could be good guidance for partner therapy to strengthen both the relationship and the partners’ well-being in it.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of social norms and cues could also negatively affect relationship quality, trust, and shared understanding in VR, which work on virtual teams have established as important for team collaboration [ 6 ]. In a separate body of work, attitude familiarity, or knowledge of another person’s attitudes, has been linked to smoother interactions with others (e.g., less conflict and more support; [ 7 ]) and reports of better relationship quality [ 8 ], suggesting that becoming familiar with a partner’s attitudes may facilitate performance in VR where normal social cues can be lacking. The goal of the current research was to investigate whether increasing attitudinal familiarity between team members could improve team performance in VR environments.…”
Section: Introductionmentioning
confidence: 99%
“…A follow up study found that more familiar couples also reported that they were less likely to fight, less likely to upset one another, more likely to be helpful, and perceived their relationships as more important [ 7 ]. Furthermore, attitude familiarity was associated with higher levels of marital satisfaction and satisfaction with life [ 8 ]. However, the above work is correlational and conducted exclusively with romantic couples.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have been conducted on value/attitude similarity on relationship satisfaction suggest small or negligible effects (e.g., Gaunt, 2006;Luo & Klohnen, 2005;Moore, Uchino, Baucom, Behrends, & Sanbonmatsu, 2017); however, these studies have often been hampered by methodological issues (e.g., use of profile correlations or difference scores as indices of similarity).…”
Section: Spousal Similarity and Relationship Satisfactionmentioning
confidence: 99%